HOW DO READING MOTIVATION AND STORYTELLING TECHNIQUE AFFECT STUDENTS’ COMPREHENSION OF READING AT SMA N 1 SEMENDE DARAT LAUT - Siti Aisah; Artanti Puspita Sari; Masagus Firdaus (PROJECT (Professional Journal of English Education), 2023)
This article aims to look at: (1) the differences that occur between reading motivation and storytelling techniques on students' reading comprehension, and (2) the interactions that occur between the independent variables, moderator variables and dependent variables. In this study used descriptive techniques using descriptive analysis methods to analyze the data, where the data obtained will be analyzed in the form of words or numbers. This study used 33 class XI students of SMA Negeri 1 Semende Darat Laut as respondents. From the research findings, there is a difference between variable X1 Motivation to Read and Variable X2 storytelling technique towards the variable y reading comprehension, and there has been a significant interaction between the variables in the research. based on these findings the researcher can draw conclusions from this analysis, as follows: Students' reading comprehension is influenced by storytelling strategies and reading motivation.